Updated Clinical Classification of Pulmonary Hypertension - Simonneau, Gérald; Robbins, Ivan M.; Beghetti, Maurice; Channick, Richard N.; Delcroix, Marion; Denton, Christopher P.; Elliott, C. Gregory; Gaine, Sean P.; Gladwin, Mark T.; Jing, Zhi-Cheng; Krowka, Michael J.; Langleben, David; et al. (Journal of the American College of Cardiology, 2009)
The aim of a clinical classification of pulmonary hypertension (PH) is to group together different manifestations of disease sharing similarities in pathophysiologic mechanisms, clinical presentation, and therapeutic approaches. In 2003, during the 3rd World Symposium on Pulmonary Hypertension, the clinical classification of PH initially adopted in 1998 during the 2nd World Symposium was slightly modified. During the 4th World Symposium held in 2008, it was decided to maintain the general architecture and philosophy of the previous clinical classifications. The modifications adopted during this meeting principally concern Group 1, pulmonary arterial hypertension (PAH). This subgroup includes patients with PAH with a family history or patients with idiopathic PAH with germline mutations (e.g., bone morphogenetic protein receptor-2, activin receptor-like kinase type 1, and endoglin). In the new classification, schistosomiasis and chronic hemolytic anemia appear as separate entities in the subgroup of PAH associated with identified diseases. Finally, it was decided to place pulmonary veno-occlusive disease and pulmonary capillary hemangiomatosis in a separate group, distinct from but very close to Group 1 (now called Group 1′). Thus, Group 1 of PAH is now more homogeneous.